Aerial imagery datasets of permafrost landscapes in Alaska and northwestern Canada acquired by the Modular Aerial Camera System - Rettelbach, Tabea; Nitze, Ingmar; Grünberg, Inge; Hammar, Jennika; Schäffler, Simon; Hein, Daniel; Gessner, Matthias; Bucher, Tilman; Brauchle, Jörg; Hartmann, Jörg; Sachs, Torsten; Boike, Julia; et al. (PANGAEA, 2024)
During three airborne campaigns conducted between 2018 and 2021 and led by the Alfred Wegener Institute, we collected super-high-resolution multispectral imagery of permafrost landscapes using the Modular Aerial Camera System (MACS) developed by the German Aerospace Center. The images, covering regions in northwestern Canada and Alaska, were processed into four-band orthophotos, digital surface models, and photogrammetric point clouds with spatial resolutions ranging from 7 to 20 cm. This dataset offers unprecedented insights into transitioning permafrost environments as it provides an essential resource for generating detailed training data, establishing baselines for detecting changes related to thermokarst and thermo-erosion processes, and facilitating the translation of field measurements to satellite observations with lower resolutions.
Keywords: airborne; Alaska; Arctic; Arctic Landscape Dynamics; Canada; coastal erosion; Digital Surface Model; MACS; Modular Aerial Camera System; NIR; Orthoimagery; Permafrost; point clouds; RGB; Structure-from-Motion; thermokarst